Evaluation of Subsidized Fertilizer Distribution to Corn Farmers in Ogan Komering Ulu Regency - Sahroni, Sahroni; Munajat, Munajat; Sari, Yunita (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2022)
This study reviewed the Evaluation of Subsidized Fertilizer Distribution in Corn Farmers in Ogan Komering Ulu Regency, South Sumatra Province. This research aims to analyze the distribution of subsidized fertilizer from producers to farmers of corn crops whether it is following the applicable rules, and to analyze the constraints in the distribution of subsidized fertilizer to corn crop farmers in Ogan Komering Ulu Regency, South Sumatra Province. The research method used is the survey method. The respondents of the study were corn farmers in Ogan Komering Ulu Regency as many as 105 people. Data analysis uses quantitative descriptive analysis techniques with the help of Likers Approximation by using scores on each question item in the questionnaire by making the highest answer to the highest answer "1" precise and lowest score "0", Not Exactly. The data that has been indicated is then determined by the overall questionnaire percentage by grouping the data by the type of statement. Furthermore, the results obtained are interpreted using the percentage category based on the criteria for assessing the accuracy of subsidized fertilizer distribution, and using Quantitative Descriptive Analysis with the help of the Problem List Table is to use an alternative answer on each question item in the questionnaire by making an alternative "Yes" answer and an authentic "No" answer. The data that has been indicated is then determined by the overall questionnaire percentage by grouping the data by the type of statement. Furthermore, the results are interpreted using the percentage category based on the criteria for assessing the constraints of subsidized fertilizer distribution. The results of this study found that the implementation of subsidized fertilizer distribution at the research site, namely Ogan Komering Ulu Regency, especially in Lengkiti District, East Baturaja District, and Sosoh Buay Rayap District has been carried out following the implementation instructions that have been set. But there are still problems that occur such as the Highest Retail Price (HIDR) and the use of Farmer Cards that have not been implemented in the field. Fertilizer subsidy policies are measured in six precise indicators, type, quantity, price, place, time, and quality. Based on the six indicators, 2 indicators of place and quality are categorized very precisely / according to the rule, while for 2 indicators of the type and the quantity can be categorized appropriately / quite according to the rule. Timely indicators can be categorized as inappropriate / not following the rules, while the price indicators for fertilizer subsidy policies can be categorized as inappropriate/very not following the rules due to the problem of price gaps in subsidized fertilizers in farmers, Line III (distributors) sell subsidized fertilizers above the Highest Retail Price (HRP) to Line IV (official kiosks) because there are additional transportation and loading and unloading costs and purchases with a pay system after harvest. Thus causing retailers to also sell subsidized fertilizer to farmers above the Highest Retail Price (HRP).